PERBANDINGAN PERHITUNGAN PPH PASAL 21 BUKAN PEGAWAI SEBELUM DAN SESUDAH PENERAPAN PP 58/2023 - Keilan Rezkia Mumtaazah; Mohammad Benny Alexandri (Politeknik Ubaya, 2025)
Government Regulation Number 58 Year 2023 was passed by the President with the aim of improving efficiency, fairness, and simplification in the taxation system. This regulation changes the mechanism for calculating Income Tax Article 21 by introducing the concept of Average Effective Rate, which comes into effect on January 1, 2024. This study aims to determine the difference in the amount of Income Tax Article 21 before and after the implementation of Government Regulation Number 58 Year 2023. The method used is a qualitative method with a legislative and comparative approach, and is accompanied by calculation simulations of three data sets. The results show that the amount of Income Tax Article 21 deducted based on the calculation in accordance with Government Regulation 58 Year 2023 tends to be greater than the previous calculation. However, this change in mechanism does not affect the total Income Tax Article 21 for one fiscal year, as the annual calculation still uses the same method as before. This change actually has an impact on the amount of tax paid by personal taxpayers in the Annual Tax Return.